ABSURD, CZYLI PYTANIE O SENS LUDZKIEJ EGZYSTENCJI. ŻÓŁTA STRZAŁA WIKTORA PIELEWINA - Baczewska-Murdzek, Agnieszka (Acta Neophilologica, 2017)
The world in which the heroes of Victor Pelevin’s novel live is a claustrophobic world. The author situates his characters in a destructive space. A Yellow Arrow, a train on the deck of which the action takes place, flashes without stopping at the destroyed bridge. It can be read either as a metaphor for human life marked by the absurdity of existence, or as a grotesque image of Russia’s transition. Turning to what is twisted, Pelevin states that the absurd can be overcome when one realises its existence and communicates with the world of absolute values.